Encounters at the counter: the organization of shop interactions - Fox, Barbara A.; Mondada, Lorenza; Sorjonen, Marja-Leena (Studies in interactional sociolinguistics, 2023)
"This volume focuses on interactions in shops, exploring the dynamics of conversation between sellers and customers. Beginning with the emergence of a 'need' for a product before the request to a seller is actually made, all the way through to the payment phase, it explores the rich and deeply methodical practices employed by customers and sellers as they go about the apparently mundane work of buying and selling small items. It looks at how seller and customer interact both verbally, and by means of manipulating the material objects involved, across a range of different kinds of purchase. Providing new insights into multimodal human interaction and the discourse of commercial activity, it aims to bring about a new understanding of the fundamental ways in which economic value, possession and ownership is achieved"--